Prove (x+y)^2=x^2+2xy+y^2
2 answers:
First, you want to expand the equation so it'll be: x^2+2yx+y^2=x*2+2xy+y^2
Then you subtract y^2 from both sides: x^2+2yx+y^2-y^2=x*2+2xy+y^2-y^2
After that, you simplify: x^2+2yx=x*2+2xy
And subtract x^2+2xy from both sides: x^2+2yx-(x*2+2xy) =x*2+2xy-(x*2+2xy)
Finally, you simplify to get your final answer which is <em>x=2, x=0</em>
Rules of exponents and the distributive property apply.
(x+y)² = (x+y)·(x+y) . . . . . meaning of exponent of 2
= x·(x+y) +y·(x+y) . . . . . . . distributive property
= x·x +x·y +y·x +y·y . . . . . distributive property
= x² +x·y +x·y +y² . . . . . . meaning of exponent of 2, commutative property of multiplication
= x² +(1+1)·x·y +y² . . . . . . distributive property
= x²+2xy+y² . . . . . . . . . the desired form
Thus
(x+y)² = x²+2xy+y²
You might be interested in
11/12 as a fraction is 11/12; as a decimal it is ~ 0.9167
Answer: 0.0083
0.00083
0.000083
Step-by-step explanation: hope it helps
Answer:
19
Step-by-step explanation:
Answer:
n + 32 = 59.13
Step-by-step explanation:
n + 32 = 59.13
Havent done this in years but i think it would just be 12